Upper critical magnetic field and vortex-free state in very thin epitaxial d-MoN films grown by polymer-assisted deposition - Haberkorn, Nestor Fabian (2013)
We measured the thickness dependence of the superconducting properties in epitaxial δ-MoN thin films grown on α-Al2O3(001) substrates by polymer-assisted deposition. Our results indicate that the superconducting properties such as the upper critical field (μ0Hc2 ≈ 10 T) and the superconducting critical temperature (Tc = 12.5 K) are thickness independent for films thicker than ~36 nm. By measuring the critical current density (Jc) in the vortex-free state, which coincides with the depairing current density (J0), we estimate that films thicker than ~36 nm have a coherence length ξ(0) = 5.8 ± 0.2 nm and penetration depth λ(0) = 420 ± 50 nm. We found that it is possible to enhance the Hc2(0) values to close to 10 T without any appreciable reduction in Tc.